Improving the Efficiency of Production Process Organization in the Resource Saving System of Petrochemical Enterprises - Shinkevich, Alexey I.; Kudryavtseva, Svetlana S.; Shinkevich, Marina V.; Salimianova, Indira G.; Ishmuradova, Izida I. (International Journal of Energy Economics and Policy, 2019)
The relevance of this study is determined by the fact that the issues of resource-saving technology implementation in the petrochemical complex have not been fully addressed yet and require further study and systematization of the determining factors, which is especially important on the back of the emergence and development of "green" industries and the digital economy in Russia. The purpose of the article is to identify the factors of the resource saving system and the extent, to which digital technologies are used by petrochemical enterprises. The main research methods underlying the article include the method of description used to identify trends in the waste production and consumption in petrochemical facilities; component analysis method, which helped to identify three groups of criteria factors affecting the resource saving system of the petrochemical industry, depending on the level of its digitalization; factor analysis method used to compile the indicators of digital technologies application in the petrochemical complex into three groups; and production function modeling for the petrochemical industry, taking into account the digital physical and digital human capital. The paper analyzes the resource saving system in the Russian petrochemical complex; the resource saving system of the petrochemical industry has been modeled, depending on the level of its digitalization; also the study provides a production function model for the petrochemical industry, which may be used to model the parameters and the resulting indicators of the resource saving system in the petrochemical industry. The information contained in the article can be used to develop strategies and programs aimed at the improvement of the resource-saving system efficiency in petrochemical enterprises, taking into account the requirements for production digitalization and the ratio of digital physical to digital human capital. Keywords: resource saving, petrochemical enterprise, petrochemical complex, production efficiency, digital technologies JEL Classifications: D24; Q43; M31 DOI: https://doi.org/10.32479/ijeep.7966